A Comparative Study of al-Jarḩ wa al-Ta‘dīl in Ahl al-Sunnah and Shī‘ah Imāmiyyah - Muhammad Azzam; Muhammad Akhyar; Muhammad Akbar Tanjung; Neni Nurlaela; Mulyana (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The science of al-Jarḩ wa al-Ta‘dīl occupies a central position in hadith criticism as the primary instrument for evaluating the credibility of hadith narrators. Ahl al-Sunnah developed this discipline around the criteria of ‘adālah and ḍabṭ, while Shī‘ah Imāmiyyah developed a parallel discipline known as ‘Ilm al-Rijāl, which places strong emphasis on a narrator's loyalty to Ahl al-Bayt. This methodological divergence carries significant implications for the corpus of hadith accepted by each school, yet a focused comparative study of the two traditions remains limited. This study aims to compare the concepts, criteria, and epistemological foundations of al-Jarḩ wa al-Ta‘dīl in the Sunni tradition with ‘Ilm al-Rijāl in the Imāmī Shī‘ah tradition, and to examine how these methodological differences shape the acceptance of contested hadith such as the hadith of Ghadīr Khum and the hadith of the twelve caliphs. This research employs a qualitative library research design with a thematic (mawḍū‘ī) approach, a descriptive-analytical method, documentation as the data collection technique, and content analysis as the data analysis technique. Primary sources include Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, and classical rijāl literature from both traditions, supported by relevant secondary scholarship. The findings show that although both schools share the goal of safeguarding the authenticity of hadith and use comparable narrator classifications such as thiqah and ḍa‘īf, they differ fundamentally in their standards for evaluating the Companions, their sources of religious authority, and the resulting corpus of accepted hadith. These differences are not merely technical but reflect divergent paradigms in understanding religious authority and the transmission of Islamic teachings.